2010
DOI: 10.1002/ajmg.b.31127
|View full text |Cite
|
Sign up to set email alerts
|

A genomewide linkage study on suicidality in major depressive disorder confirms evidence for linkage to 2p12

Abstract: Suicidal behavior is commonly associated with depression. Twin studies indicate that both suicidality and major depressive disorder (MDD) are heritable. However, epidemiological evidence suggests that the inheritance of suicidality is likely to be independent of the underlying psychiatric disorder, implying a distinct genetic contribution to suicidality. We conducted a genomewide linkage search aiming to detect genomic loci that may harbor susceptibility genes contributing to risk for suicidality in recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…Twin, adoption and family studies have indicated that both suicidal behaviour and MDD are genetically modulated (Brent and Mann, 2005;Butler et al, 2010). It is estimated that ∼ 30 million individuals per year are affected by MDD within the European Union, with a lifetime risk for suicide with up to 15% (Davies et al, 2001;Wittchen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Twin, adoption and family studies have indicated that both suicidal behaviour and MDD are genetically modulated (Brent and Mann, 2005;Butler et al, 2010). It is estimated that ∼ 30 million individuals per year are affected by MDD within the European Union, with a lifetime risk for suicide with up to 15% (Davies et al, 2001;Wittchen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Only GWAS which assayed SNPs were included. Linkage studies were excluded and have been reviewed elsewhere (Butler et al, 2010). Power for single SNP-associations (Table 1) …”
Section: Methodsmentioning
confidence: 99%
“…However, a combined meta-analysis analysis of both the discovery and replication samples yielded a genome-wide significant association for SNP rs300774 (which also showed the lowest p-value in the discovery sample). LD-analysis of SNP rs300774 showed it was located in a large LD-block containing three genes (SH3YL1, ACP1 and FAM150B), as well as being near a consistently demonstrated linkage peak (at 2p11-12) for suicide attempts (Butler et al, 2010). Strength of the study is that they then assessed gene-expression data and found RNA expression changes in the prefrontal cortex of bipolar suicides for ACP1 (but not SH3YL1) and thus proposed the SNP association to be involved in ACP1 functions.…”
Section: Suicidal Behavior Outcomesmentioning
confidence: 99%
“…In a recent report, Butler et al [2010] presented the results of a genome-wide linkage analysis of a quantitative suicidality trait in recurrent Major Depressive Disorder (R-MDD). Although the investigators failed to find genome-wide significant linkage at any region, they reported evidence in support of linkage near D2S1777 on chromosome 2p12, as well as meta-analysis of previous linkage analyses in the region that yielded a combined P-value of 2 Â 10…”
Section: To the Editormentioning
confidence: 99%
“…The studies chosen by Butler et al for consideration in their meta-analysis included families ascertained through different diagnostic phenotypes, and these studies employed different affected mood phenotypes, diverse suicide phenotypes, and different statistical methods for linkage analysis. Furthermore, in an attempt to replicate the results of their MSP meta-analysis, we can approximate their findings (P $ 10 À6 ) only by including the results from the Butler et al [2010], Willour et al [2007], and Hesselbrock et al [2004] studies, and excluding the results reported in the studies of Cheng et al [2006] and Zubenko et al [2004]. Importantly, these first three studies are exclusively those that Butler et al contend reported previous positive findings, an approach that would lead to a biased estimate.…”
Section: à6mentioning
confidence: 99%